Evaluation of genetic damage in a Brazilian population occupationally exposed to pesticides and its correlation with polymorphisms in metabolizing genes - Juliana da Silva; Cássia Regina Cabral de Moraes; Vanina D. Heuser; V. M. Andrade; Fernanda Rabaioli da Silva; Kátia Kvitko; V.E. Emmel; Paula Rohr; Diana L. Bordin; Ana C. Andreazza; Miriam Salvador; João Antônio Pêgas Henriques; et al. (2008)
Cytogenetic damage in individuals occupationally exposed to pesticides has received the attention of investigators in several countries, but no definitive conclusions can yet be made. The present study aimed at assessing if prolonged exposure to complex mixtures of pesticides leads to an increase in cytogenetic damage. Vineyard workers exposed to pesticides in Caxias do Sul (Brazil) were evaluated using the micronucleus (MN) test in binucleated lymphocytes and the comet assay in peripheral leukocytes. In order to evaluate if genetically determined individual variations in xenobiotic metabolizing capacity could modify individual susceptibility to the possible genotoxic effects of pesticides, the subjects were genotyped for several genes: GSTT1, GSTM1, GSTP1, CYP1A1, CYP2E1 and PON. The study involved a total number of 173 men: 108 were agricultural workers exposed to pesticides and 65 were controls. The present study showed a high rate of MN and DNA damage in pesticide-exposed individuals (P <or= 0.001; Mann-Whitney U-test). In addition, some effects of genetic polymorphisms in PON in the modulation of MN results were observed in the exposed group, and an association between GSTM1, GSTT1 and CYP2E1 polymorphisms was suggested.